1991
DOI: 10.1136/adc.66.6.683
|View full text |Cite
|
Sign up to set email alerts
|

Changes in periurethral microflora after antimicrobial drugs.

Abstract: The periurethral flora was examined in 18 girls by use of a quantitative sampling method before, during, and three weeks after treatment with antibiotics for upper respiratory tract infections. Eight girls received amoxicillin. In five of them the anaerobic flora showed a reduction in total counts and in numbers of different species, and ali eight girls got a heavy colonisation with enterobacteria during treatment. Three weeks after treatment the anaerobic and aerobic flora had reversed to the pretreatment com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…A 5-mL plastic syringe filled with 12% sterile gelatine (Difco Laboratories, USA) was cut at the needle end of the syringe and gelatine was pressed against the skin surface for 10 seconds without rotation. A 2-mm slice of gelatine with the bacterial bearing surface (approximately area 1 cm 2 ) was cut-off, put in a sterile glass tube with 2 mL prereduced peptone-yeast-glucose (PYG) medium (Difco Laboratories, Detroit, MI, USA) and immediately transported to the laboratory, as previously described for the collection of the skin microflora (Borglund et al, 1984;Lidefelt et al, 1991;Sullivan et al, 2001b). It was shown previously that the follicular casts from patients colonized with high numbers of resistant bacteria on the skin surface not always contain antibiotic resistant P. acnes.…”
Section: Sampling and Microbiological Procedures (Papers I Iv And V)mentioning
confidence: 99%
“…A 5-mL plastic syringe filled with 12% sterile gelatine (Difco Laboratories, USA) was cut at the needle end of the syringe and gelatine was pressed against the skin surface for 10 seconds without rotation. A 2-mm slice of gelatine with the bacterial bearing surface (approximately area 1 cm 2 ) was cut-off, put in a sterile glass tube with 2 mL prereduced peptone-yeast-glucose (PYG) medium (Difco Laboratories, Detroit, MI, USA) and immediately transported to the laboratory, as previously described for the collection of the skin microflora (Borglund et al, 1984;Lidefelt et al, 1991;Sullivan et al, 2001b). It was shown previously that the follicular casts from patients colonized with high numbers of resistant bacteria on the skin surface not always contain antibiotic resistant P. acnes.…”
Section: Sampling and Microbiological Procedures (Papers I Iv And V)mentioning
confidence: 99%
“…Since the gram negative bacilli cultured from the urethra were most likely from the fecal¯ora, it is also possible that this observation re¯ects an indirect e ect of antibiotics on the bowel¯ora that has been described previously. 12,13 …”
Section: Discussionmentioning
confidence: 99%
“…A study by Lidefelt et al showed that girls treated with amoxicillin for upper respiratory tract infections showed a significant drop in anaerobic periurethral flora and a heavy colonisation with enterobacteria during treatment. However, this effect was not observed when the upper respiratory tract infections were treated with trimethoprimsulfamethoxazole [18]. Another study identified prior penicillin V treatment as a risk factor for the development of pyelonephritis in infants and pre-school children and, although not demonstrated, destruction of the commensal microflora can be inferred [19].…”
Section: Factors To Consider For Reduction Of Antimicrobial Resistancementioning
confidence: 94%